Mobile and handheld computing solutions for organizations and end-users - Hu, Wen Chen, 1960-; Mousavinezhad, S. Hossein, 1947- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"This book discusses a broad range of topics in order to advance handheld knowledge and apply the proposed methods to real-world issues for organizations and end users"--Provided by publisher.